Development of a low-firepower continuous feed biomass combustor - Rayno, Mars, author; Mizia, John, advisor; Windom, Bret, advisor; Carter, Ellison, committee member (Colorado State University. Libraries, 2020)
Approximately 25% of world's population lacks basic sanitation amenities. This lack of sanitation leads directly to the spread of contagious diseases and parasites. One method that can help mitigate these consequences is the thermal treatment of human feces in a combustion system. Colorado State University's Advanced Biomass Combustion Lab has been working on thermal treatment systems as part of the Bill and Melinda Gates Foundation Reinvent the toilet challenge for over 7 years. The goal is to develop stand-alone treatment technologies that can process waste for less than 5 cents per person per day. Thermal processing is an attractive solution because it not only destroys pathogens, but also significantly reduces the amount of mass that needs to be disposed of. Until recently, the focus has been on larger (2 kW) fecal gasifiers. This scale of combustor was designed to incinerate the solid waste of approximately 28 users per hour. The large amount of users required to operate meant that either fuel would need to be stored before usage or the combustor would be subject to frequent startups and shutdowns. During steady state operation the gasifier emits low quantities of harmful pollutants, but during startup and shutdown the emissions are considerably higher. Thus, there is a need to mitigate or reduce the frequency of those transient events. One way to address this problem is to develop a suite of scaled combustors. A 500 W combustor, for example, would be able to run continuously for 12 hours with 30 users, or 24 hours with 60 users. This project investigated a scaled version of the 2kW fecal combustor developed under the BMGF RTTC. Emission factors for this scaled device were generated for various firepowers, air-fuel ratios, and primary-to-secondary air ratios.